Application of a MOF separation material in N2 / O2 separation

By using chromium and H3BTC-synthesis of MOF material MSK-96Cr with microporous structures, the problems of high energy consumption and low O2 production efficiency in the existing air separation technology are solved, efficient N2/O2 separation is achieved, and the purity of O2 is improved. and yield, suitable for medium or portable oxygen supply needs.

CN113908808BActive Publication Date: 2024-12-17ZHENGZHOU MISHKA CHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110669732.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-17
Publication Date
2024-12-17
Estimated Expiration
2041-06-17

AI Technical Summary

Technical Problem

Existing air separation technologies, especially low-temperature distillation and temperature/pressure-switching adsorption (PSA) methods, have problems with high energy consumption and limited O2 production efficiency when producing high-purity oxygen, and are difficult to meet the needs of medium or portable oxygen.

Method used

The MOF material MSK-96Cr synthesized with microporous structures is improved by chromium and H3BTC, through its unique metal cluster structure and pore space, and achieves efficient N2 adsorption and O2 selectivity.

Benefits of technology

MSK-96Cr significantly improves N2 adsorption capacity and O2 selectivity, reduces the gas adsorption equilibrium time, and can directly recover high-purity O2 products from the adsorption cycle, with higher O2 yield and more stable structure, suitable for medium or Portable oxygen supply application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113908808B_ABST
    Figure CN113908808B_ABST
Patent Text Reader

Abstract

The present invention discloses an application of a MOF separation material in N2 / O2 separation, which is an important method for producing high-purity O2. The present invention uses a chromium-based metal organic framework material, namely MSK-96Cr, whose N2 adsorption capacity is 37.46 cm 3 •cm ‑3 , N2 / O2 (10:90, v / v) selectivity is 22.45 (298 K and 1 bar). MSK‑96Cr has a high N2 adsorption capacity, which significantly shortens the gas adsorption equilibrium time; at the same time, relying on the preferential adsorption of N2 by unsaturated Cr metal sites, it can adsorb N2 with high selectivity in different N2 / O2 (50 / 50‑79 / 21, v / v) concentration ranges, especially at higher oxygen concentrations. The adsorption amount of N2 is higher than that of other adsorbent materials. For the simulated air component N2 / O2 (79 / 21, v / v), the separation efficiency is 153 mmol•L ‑1 , has good oxygen production efficiency and has great application value in the industrial production of high-purity oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal organic framework materials, and in particular to application of a MOF separation material in N2 / O2 separation. Background Art

[0002] High purity oxygen (>99%) is one of the most widely used commodity chemicals in the world, for example in medical, military, aerospace, semiconductor industry and plasma chemistry applications. Currently, air separation is the most direct way to produce high purity O2, mainly using cryogenic distillation technology with high energy consumption and large investment costs, relying only on the difference between the boiling points of N2 (77.15 K) and O2 (90.15 K). Although cryogenic distillation is a proven technology for large-scale air separation (>100 tons / year), for medium-volume or portable oxygen supply, air separation using membrane or adsorption separation processes is more economical and flexible.

[0003] Temperature / pressure swing adsorption (T / PSA) is an energy-saving air separation method and a widely used green technology method today. The PSA process requires an adsorbent with high N2 adsorption capacity and N2 / O2 selectivity. Li-LSX (lithium low-silicon X-type zeolite molecular sieve) shows good air separation yield. Li-LSX has high N2 adsorption capacity and high N2 / O2 selectivity. This is because in the lithium-containing molecular sieve channel, compared with O2 (N2 is -1.4 D, while O2 is -0.4 D), N2 has a larger quadrupole moment, resulting in a stronger interaction. However, due to the fixed structure of the X-type molecular sieve with Si, O and Al as the main skeleton, the O2 production efficiency of Li-LSX has reached its limit and is difficult to break through (JJ Potoff, JI Siepmann, AlChE J.2001, 47, 1676.). Jeffrey R. Long (ED Bloch, LJ Murray, WL Queen, S.Chavan, SN Maximoff, JP Bigi, R. Krishna, VK Peterson, F. Grandjean, GJ Long, B. Smit, S. Bordiga, CM Brown, JR Long, J. Am. Chem. Soc. 2011, 133, 14814; b) LJ Murray, M. Dinca, J. Yano, S. Chavan, S. Bordiga, CM Brown, JR Long, J. Am. Chem. Soc. 2010,132, 7856.) et al. proposed some methods to achieve highly selective adsorption of O2. These porous materials adsorb O2 more strongly than N2, which is mainly due to the strong O2 binding affinity between low-valent metal centers (such as Cr (II) and Fe (II)) and O2. However, in order to achieve high-purity oxygen, additional desorption or heating regeneration processes are required, which consumes a lot of energy.

[0004] In order to obtain a separation material with higher N2 / O2 separation effect, the present invention uses MOF material MSK-96Cr to separate N2 / O2. Summary of the invention

[0005] The present invention is an application of MOF separation material in N2 / O2 separation, and its specific technical solution is:

[0006] Application of a MOF separation material in N2 / O2 separation, wherein the MOF separation material is MSK-96Cr, wherein the MSK-96Cr is MSK-96Cr synthesized from chromium with a microporous structure and H3BTC, and wherein the molecular formula of the MSK-96Cr is Cr 12 O-(OH / F) 16 (H2O)5[BTC]6·nH2O.

[0007] Specifically, the MSK-96Cr includes two metal clusters, namely Cr (1) and Cr (2), wherein Cr (1) is a tricyclic cluster centered on carbonyl oxide, and its structure is similar to the metal site in MIL-100Cr, while Cr (2) exists in another tricyclic cluster. Both metal clusters can produce unsaturated metal sites.

[0008] Furthermore, the MSK-96Cr contains three types of pores, a closed cage with a narrow window size (1.2Å×1.9Å) and an elliptical window connected (7.2Å×6.8Å), thereby forming a zigzag pore structure in MSK-96Cr; during the activation process, after the coordinated water molecules are removed, the window size will increase;

[0009] Furthermore, the high-density Cr (III) unsaturated sites of the MSK-96Cr form a strong interaction with N2 to achieve N2 / O2 separation;

[0010] The preparation method of the MSK-96Cr is:

[0011] Add metallic chromium and tricarboxylic acid, H3BTC into a polytetrafluoroethylene reactor, add a water / methanol mixed solution and hydrofluoric acid into the reactor and mix. Stir the mixture evenly. After stirring, seal the polytetrafluoroethylene reactor in a stainless steel shell, put it into an oven for heating and keep it for a period of time, then take out the reactor and cool it naturally to room temperature. The light green product obtained by the reaction is first filtered, then washed with distilled water and methanol respectively, and dried to obtain MSK-96Cr.

[0012] The molar ratio of the metal chromium to H3BTC is 1-2:1, and the molar ratio of the metal chromium to hydrofluoric acid is 1:1-3;

[0013] The stirring condition is stirring at 298K for 15-30min;

[0014] The heating conditions are as follows: the oven temperature is raised from room temperature to 473-493 K within 10-16 h and maintained at this temperature for 96 h;

[0015] The distilled water dosage is: 200-280 ml / g product, the methanol dosage is 200-280 mL / g product, and the washing times are 3-5 times;

[0016] The oven temperature was raised from room temperature to 483 K within 12 h and maintained at 483 K for 96 h, and then the reactor was taken out and naturally cooled to room temperature. The light green product obtained by the reaction was first filtered and then washed three times with 1 g / 250 mL distilled water and 1 g / 250 mL methanol at 353 K to remove excess unreacted organic ligands. Then, the obtained MSK-96Cr was dried at 323 K.

[0017] Technical effect:

[0018] The mechanism of the present invention is that the d3 electronic configuration unsaturated metal (V (II) or Cr (III)) site has a special binding affinity with N2, thereby preparing the chromium and H3BTC-based microporous MOF MSK-96Cr, which has two active open Cr (III) sites and a more suitable pore environment. Based on the optimized pore space, it has more Cr (III) unsaturated sites per unit cell on average, and has better N2 adsorption effect than MIL-100Cr (currently reported as the best N2 / O2 separation material). The content of Cr (III) unsaturated sites in MSK-96Cr is 3.34 mmol•cm -3 , which is higher than 2.42 mmol•cm in MIL-100Cr -3 ; In addition, the moderate adsorption heat of MSK-96Cr not only makes MSK-96Cr have a higher N2 adsorption capacity, but also greatly reduces the gas adsorption equilibrium time; at the same time, the preferential adsorption of N2 can directly recover the required high-purity O2 product from the adsorption cycle.

[0019] Cr(1) is a tricyclic cluster centered on carbonyl oxide, which is similar to the metal site in MIL-100Cr, while Cr(2) is present in another unusual tricyclic cluster. Both clusters may generate unsaturated metal sites after removal of the terminal solvent molecules. Theoretically, the content of Cr(III) unsaturated sites in MSK-96Cr is higher than that in MIL-100Cr (3.34 vs. 2.42 mmol•cm -3 ). Therefore, MSK-96Cr can show higher N2 adsorption capacity and N2 / O2 adsorption selectivity, thus significantly improving the N2 separation performance.

[0020] MSK-96Cr has three types of pores: pores A, B, and C; A is a closed cage with a narrow window size (1.2Å×1.9Å), B and C are connected by an elliptical window (7.2Å×6.8Å), forming a zigzag pore structure in MSK-96Cr. Generally, during the activation process, after the coordinated water molecules are removed, the window size between B and C will increase, which is beneficial to the adsorption of gases.

[0021] MSK-96Cr has a high adsorption capacity for N2 and has good adsorption for N2 in different N2 / O2 (50 / 50-79 / 21, v / v) ranges. Especially at higher oxygen concentrations, the adsorption capacity for N2 is higher than that of other adsorption materials.

[0022] MSK-96Cr has good selectivity. Compared with other adsorbents, its selectivity in N2 / O2 (50 / 50, v / v) can reach 13, which is much higher than the materials reported at this stage.

[0023] The oxygen production is much higher than that of MIL-100Cr. The production can reach 153mmol•L under N2 / O2 (79 / 21, v / v) -1 , which is also much higher than the oxygen production of MIL-100Cr. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 . Framework structure and open metal sites of MSK-96Cr;

[0025] Figure 2 . Schematic diagram of three different types of pores in MSK-96Cr;

[0026] Figure 3 a) Rietveld refined XRD pattern of MSK-96Cr; b) N2 adsorption isotherm of MSK-96Cr at 77 K; c) Thermogravimetric curves of MSK-96Cr and MIL-100Cr; d) PXRD patterns of MSK-96Cr samples after treatment under different conditions;

[0027] Figure 4 .N2 adsorption diagram of various adsorption materials at 0-1 bar;

[0028] Figure 5 . N2 / O2 adsorption selectivity of common porous materials;

[0029] Figure 6 . Breakthrough curves of various adsorption materials at different N2 / O2 mixing ratios;

[0030] Figure 7 . Breakthrough curves of MSK-96Cr at different N2 / O2 mixing ratios at 5 bar. DETAILED DESCRIPTION

[0031] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0032] Example 1

[0033] MSK-96Cr preparation:

[0034] Metallic chromium powder (104 mg, 2 mmol) and H3BTC (280 mg, 1.34 mmol) were added to a 50 mL polytetrafluoroethylene reactor, and then, 10 mL of a methanol / water mixed solution (1:1, v / v) and 0.8 mL of hydrofluoric acid (4 mmol) were added to the reactor using a pipette. The above mixture was stirred at 298 K for 0.5 h. After the stirring was completed, the polytetrafluoroethylene reactor was sealed in a stainless steel shell and placed in an oven. The oven temperature was increased from room temperature to 483 K within 12 h and maintained at 483 K for 96 h, and then the reactor was taken out and naturally cooled to room temperature. The light green product obtained by the reaction was first filtered, and then washed with distilled water and methanol at 353 K for 3 times at a ratio of 1 g product / 250 mL distilled water and 1 g product / 250 mL methanol, respectively, to remove excess unreacted organic ligands. The obtained MSK-96Cr product was then dried at 323 K.

[0035] Gas adsorption test:

[0036] The single-component gas adsorption isotherms of N2 and O2 and the N2 adsorption kinetics were measured using an intelligent gravimetric analyzer (IGA 001, Hiden, UK). The nitrogen adsorption and desorption isotherms of the samples at 77 K were measured using an APSP 2020 analyzer. Unless otherwise stated, the samples were heated at 523 K and 1 × 10 -5 After 5 hours of activation, the test was performed again.

[0037] Structural analysis:

[0038] The TOPAS software (CCDC: 2017985) was used for Rietveld refinement ( Figure 3 a) The structure of the MOF was accurately analyzed. The chemical formula of MSK-96Cr was determined to be Cr 12 O-(OH / F) 16(H2O)5[BTC]6·nH2O; The structure includes two forms of metal open sites: Cr (1) and Cr (2), with a ratio of 1:2 respectively;

[0039] MSK-96Cr has three types of holes: holes A, B and C, such as Figure 2 As shown: A is a closed cage with a narrow window size (1.2Å×1.9Å), and B and C are connected by an elliptical window (7.2Å×6.8Å), forming a zigzag pore structure in MSK-96Cr. Usually, during the activation process, the window size between B and C will increase after the coordinated water molecules are removed.

[0040] The crystal data calculated from the Rietveld refined XRD pattern of MSK-96Cr are: Rewp = 4.57%, Rwp = 4.84%, Rp = 4.72%, GOF = 1.06, a = b = 14.27Å, c = 30.98Å, α = β = 90°, γ = 120°; Figure 3 b N2 adsorption isotherm of MSK-96Cr at 77 K is a type I adsorption isotherm, indicating that MSK-96Cr is a microporous material.

[0041] Stability analysis

[0042] The TG curves of MSK-96Cr and MIL-100Cr show that the unsaturated Cr (III) sites on MIL-100Cr are the key to binding gas molecules, but the coordinated water molecules on the Cr (III) sites need to be placed under extremely high temperature (523 K, close to the decomposition temperature of MIL-100Cr) and high vacuum (10 -5 mbar, a turbomolecular pump is required), and according to the TG results ( Figure 3 c) The temperature at which MSK-96Cr maintains stability is as high as 648 K, which is much higher than the structural decomposition temperature of MIL-100Cr (about 573 K); therefore, MSK-96Cr will be more stable during the pretreatment process; in order to further verify the stability of MSK-96Cr samples after treatment under different conditions, a certain amount of two samples were soaked in water, acidic and alkaline environments, boiling water, 12 M HCl, 16 M HNO3 and 0.01 M NaOH for 12 hours, and the crystallinity of MSK-96Cr was detected by PXRD. This shows that MSK-96Cr can maintain structural stability regardless of acid or alkali.

[0043] Example 2 N2 adsorption capacity at different pressures

[0044] The N2 separation capabilities of different adsorption materials MIL-100Cr, ZIF-8, UIO-66, Co-MOF-74, Cu-BTC, MIL-101Cr, 13X, Li-LSX and MSK-96Cr materials were compared at 298 K with a gas flow rate of 15 ml / min and N2 partial pressures of 0.1 bar, 0.5 bar, 0.79 bar and 1 bar for different N2 / O2 mixed gases. The equipment used for gas adsorption was the same as that in Example 1.

[0045] according to Figure 4 The results shown in the figure show that, combined with the N2 adsorption of each adsorbent material, MSK-96Cr exhibits the highest N2 adsorption capacity within this pressure range, and the N2 adsorption capacity can reach 37.46 cm at 1 bar. 3 •cm -3 , the adsorption capacity is remarkable.

[0046] Example 3 Adsorption Selectivity Different adsorption materials MIL-100Cr, ZIF-8, UIO-66, Co-MOF-74, Cu-BTC, MIL-101Cr, 13X, Li-LSX and MSK-96Cr were used to carry out gas adsorption experiments on the above samples. The equipment used for gas adsorption was the same as that in Example 1.

[0047] At 298K and 1 bar, the selectivity results of N2 / O2 mixed gas (total pressure is 1 bar) with N2 partial pressures of 0.01 bar, 0.1 bar, 0.50 bar and 0.79 bar to N2 are shown in Figure 5 and Table 1.

[0048] Table 1 N2 / O2 selectivity of different adsorbents

[0049]

[0050]

[0051] The results show that MSK-96Cr has better adsorption selectivity than other adsorbents under several partial pressure conditions.

[0052] Example 4 Adsorbent penetration test at different N2 / O2 mixing ratios

[0053] The adsorbents MSK-96Cr, MIL-100Cr, 13X, and Li-LSX were subjected to penetration tests at 298K 1 bar with a flow rate of 15 mL / min and different N2 / O2 ratios (79:21, 50:50, v / v). The four adsorbent powders were first pressed into tablets at a pressure of 4 MPa using a tablet press, and then sieved through a stainless steel mesh into particles with a diameter of about 2 mm. The prepared MSK-96Cr, MIL-100Cr, Li-LSX, and 13X samples were subjected to penetration tests at 523 K, 1 × 10 -5 mbar conditions for 12 h, and then loaded into the adsorption column (Φ9.0 × 150 mm) in anhydrous environment. Before starting the test, the adsorption column was flushed with He gas at a flow rate of 15 mL / min and a temperature of 373 K, and then the inlet gas was switched to a mixed gas with a total gas flow rate of 15 mL / min for testing. The spectrum of the adsorption column outlet gas was recorded using an online mass spectrometer (HPR-20EGA, Hiden, UK, detection limit 0.01%) to obtain the final penetration curve.

[0054] Through the penetration curve Figure 6 By comparison, it can be seen that MSK-96Cr can effectively capture N2 from two mixtures of N2 / O2 volume ratios to obtain high-purity O2.

[0055] At the same time, based on the above samples, the pure oxygen production was tested, and the results are shown in Table 2 below.

[0056] Table 2 Pure oxygen production of adsorbents at different N2 / O2 ratios

[0057]

[0058] MSK-96Cr has a much higher pure oxygen yield than MIL-100Cr and commercially used Li-LSX, and has great industrial application value in producing high-concentration oxygen.

[0059] Example 5 N2 / O2 ratio separation experiment of MSK-96Cr under high pressure

[0060] In order to better realize the actual separation of MSK-96Cr, considering that the adsorbent usually experiences higher pressure and space velocity, the separation of N2 / O2 mixtures with different concentrations under high pressure by MSK-96Cr was further studied. The mixed gas penetration experiment was carried out at 298 K5bar with a flow rate of N2 / O2 (50:50 and 79 / 21, v / v) of 15 mL / min. The equipment and parameters used were the same as those in Example 4. The results of the penetration experiment are shown in Figure 2. Figure 7As shown, high-purity oxygen can also be produced with high separation efficiency under this condition, and MSK-96Cr can be identified as an effective adsorbent for N2 / O2 purification separation.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. Application of a MOF separation material in N2 / O2 separation, wherein the MOF separation material is MSK-96Cr, and the molecular formula of the MSK-96Cr is Cr 12 O-(OH / F) 16 (H2O)5[BTC]6·nH2O, the MSK-96Cr preferentially adsorbs N2 in the N2 / O2 mixed gas through unsaturated metal sites; The MSK-96Cr is used to separate N2 / O2 mixed gas with a N2 / O2 mixed volume ratio ranging from 1 / 99 to 79 / 21; The preparation method of the MSK-96Cr is: Add metallic chromium and H3BTC into a polytetrafluoroethylene reactor, add a water / methanol mixed solution and hydrofluoric acid into the reactor and mix; stir the mixture evenly. After stirring, seal the polytetrafluoroethylene reactor in a stainless steel shell, put it into an oven for heating and keep it for a period of time, then take out the reactor and cool it naturally to room temperature. Filter the light green product obtained by the reaction, then wash it with distilled water and methanol respectively, and dry it to obtain MSK-96Cr.

2. Use of a MOF separation material as claimed in claim 1 in N2 / O2 separation, The MSK-96Cr lattice parameters are a = b = 14.27Å, c = 30.98Å, α = β = 90°, γ = 120°.

3. The use of a MOF separation material as described in claim 1 in N2 / O2 separation, wherein there are two active metal Cr clusters, namely Cr (1) and Cr (2), wherein Cr (1) is a tricyclic cluster centered on carbonyl oxide, and Cr (2) exists in another tricyclic cluster, and both metal clusters produce unsaturated metal sites.

4. The use of a MOF separation material as claimed in claim 1 in N2 / O2 separation, wherein the MSK-96Cr comprises three types of pores, one closed cage with a narrow window size, and the other two connected by elliptical windows, thereby forming a zigzag pore structure in the MSK-96Cr.

5. The use of a MOF separation material in N2 / O2 separation according to claim 4, wherein the molar ratio of the metal chromium to H3BTC is 1-2:1, and the molar ratio of the metal chromium to hydrofluoric acid is 1:1-3; The stirring condition is stirring at 298K for 15-30 min.

6. The use of a MOF separation material in N2 / O2 separation according to claim 5, wherein the heating condition is: the oven temperature is increased from room temperature to 473-493 K within 10-16 h and maintained at this temperature for 96 h; The amount of distilled water used is 200-280 ml / g product, the amount of methanol used is 200-280 mL / g product, and the number of washing times is 3-5 times.

7. An application of the MOF separation material as claimed in claim 1 in N2 / O2 separation, wherein the MOF separation material is used to produce pure oxygen without going through an additional desorption or regeneration process.